Heavy Metals (Hg, Cd, Pb, Cu) in Greenback Mullets (Planiliza subviridis Valenciennes, 1836) from Bojonegara coastal waters, Banten Bay, Indonesia - Ghinarrahmi Afiyatillah; Sulistiono Sulistiono; Sigid Hariyadi; Charles PH Simanjuntak; Etty Riani; Rita Rostika; Sonja Kleinertz (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Waste from industrial activities can be a source of pollution for the waters of Banten Bay. One source of these pollutants are heavy metals. High concentrations of heavy metals in waters can pollute the aquatic environment, endangering all organisms. Heavy metals can accumulate in aquatic environments and living organisms such as fish. The greenback mullet Planiliza subviridis (Valenciennes, 1836) is known as a fish for human consumption. Heavy metals that are contained in mullets can move to a higher trophic level within the food chain and endanger the health of humans. This study aims to analyze the accumulation of heavy metals, such as Hg, Cd, Pb, and Cu, in the flesh of greenback mullets at Bojonegara Waters of Banten Bay. The research was carried out for five months (August - October 2020 and March - April 2021). Samplings were taken from Terate River and Wadas River, which are mullet fishing areas and natural habitats of these mullets. Data analysis consisted of descriptive and quantitative analyses. The results showed that the Hg, Cd, Pb, and Cu contents were below the quality standards based on Government Regulation of the Republic of Indonesia (PP RI) No. 22 of 2021. The greenback mullets have experienced a moderate accumulation rate. The different rates of Cu metal accumulation in each month indicate a variation in catches with low to moderate accumulation rates. The water conditions in Bojonegara can still be seen as tolerable and still suitable for mullets usable for human consumption in a reasonable amount. Monitoring and evaluation activities need to be carried out periodically for the management of the aquatic environment in Bojonegara.